Building a legal knowledge test for volleyball for third-grade students of the College of Physical Education and Sports Sciences for Girls - Khalaf , A. M. D. Naima Zaidan (International Journal of Psychosocial Rehabilitation, 2020)
Volleyball has witnessed a remarkable development in the game of volleyball, and this development included legal and skill rules, players’ specialties, playing methods and their plans, and that the modern trend is distinguished in measuring knowledge, which is one of the accurate objective evaluation methods, and occupies a great degree of importance and on which the correct behavior is based in the application of legal rules When judging, which must be used with tests related to sports, and legal knowledge is very important for balls, because the more the legal knowledge of volleyball and the methods of its application increases, the student is better able to develop her ability to arbitrate upon the evaluation test, and legal knowledge of the game of volleyball is one of the important things that should be.